Exclusive Breastfeeding For Infant Growth and Development in Medan - L. Raja, Sarma Nursani (Sumatera Medical Journal, 2019)
Breast milk is one of the most perfect nutrition to ensure the growth and development of infants in the first 6 months. Exclusive breastfeeding alleged effect on infant growth and development. The purpose of this study was to analyze the influence of exclusive breastfeeding on infant growth and development. This study is a case control study in Sering Primary Health Care Medan in 2014. Anthropometric parameter of subjecs’ children were measured and plotted in the WHO graph. Then, subjects were told to undergo a 5 minute interview to analyze the pattern of breastfeeding history. In this study, both infant growth, development, and growth and development were associated with history exclusive breastfeeding (p<0.001). Exclusively breastfed infants have good growth and optimal, in contrast to infants who are not breastfed exclusively have poor growth. It was concluded that there was an influence of breastfeeding with infant growth and development.